Effectiveness of 'Kasgot' Organic Fertilizer on the Growth and Yield of Edamame Soybean on Organic Farming - Saputra, Hidayat; Septiana, Septiana; Sari, Evi Yunita; Dulbari, Dulbari; Ahyuni, Destieka; Yuriansyah, Yuriansyah (JURNAL AGROTROPIKA, 2024)
The objectives of this study were to determine whether the application of kasgot organic fertilizer can increase the growth and yield of edamame, determine whether the effectiveness of kasgot organic fertilizer is better than non-kasgot organic fertilizer, and determine the best combination of kasgot organic fertilizer and non-kasgot organic fertilizer in increasing the growth and yield of soybeans. The treatments used: no organic fertilizer (control) (P0), non kasgot solid organic fertilizer (P1), non kasgot liquid organic fertilizer (P2), kasgot solid organic fertilizer (P3), kasgot liquid organic fertilizer (P4), non kasgot solid and liquid organic fertilizer (P5), kasgot solid and liquid organic fertilizer (P6), and non kasgot organic fertilizer and kasgot organic fertilizer (P7). The research findings indicate that the application of organic fertilizer enhances the growth and yield of soybeans compared to the control. Specifically, the combination of solid kasgot organic fertilizer (5 t ha-1) with liquid kasgot (50 ml L-1 water) produced the best plant growth and number of pods plant-1. It was also reported that the variables of number of branches, plant height, and plant wet weight significantly positively correlate with the number of pods plant-1.